Transparent api (2008)
This paper describes an approach for a Transparent API (Application Programming Interface) based in Magic LensTM. Magic Lenses are movable filters that displace over an application work area and show new views of objects viewed through that area. The transparent API proposed is a visualization mechanism that have tools distinguished by: unobstructed view of the objects in the working area, use of typical interaction elements with user of traditional interfaces, active process of data, and the possibility to use it as an additional element in any graphic user interface (GUI).